Planning Of Raw Water Distribution Network Sumberrejo Village Candipuro District Lumajang Regency: Perencanaan Jaringan Distribusi Air Baku Desa Sumberrejo Kecamatan Candipuro Kabupaten Lumajang - Ahlan Tri Yogatama; Danayanti Azmi Dewi Nusantara (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2024)
Indonesians have an average domestic water consumption of 34.2 liters/person/day while the minimum amount to meet basic human needs is 50 liters/person/day. The lack of water consumption requires a water distribution system so that minimum water consumption can be met. Sumberrejo Village is one example that does not have a water distribution network, so to meet daily water needs using ground wells. The use of earthen wells certainly has risks, namely contamination from fecal waste. Research on water distribution network planning needs to be done due to these problems. This plan aims to determine the availability of water to flow through Sumberrejo Village, water needs in the projection year, pipe dimensions, and reservoir dimensions used. This study used a quantitative descriptive method. Hydraulic analysis of piping networks using the Hazen–William method with the Epanet 2.2 auxiliary program. The results of the study found that the availability of water in Sumberrejo Village was inadequate, so it used the Gedang Sutro water source located in Sumberwuluh Village. Water demand in the projection year is 20,966 l / s at peak hour conditions. The diameter of the pipe used in this planning is 8 inches; 6 inches; 5 inches; 4 inches; 3 inches; 2.5 inches; 2 inches; 1.5 inches; 1.25 inches; 1 inch; and 0.75 inches. The reservoir used in this planning is tubular with a diameter of 11.5 m and a height of 4.5 m.